Keseimbangan Peran Istri Prajurit dalam Membangun Keharmonisan Keluarga Militer: Studi Fenomenologi di Malang Raya - 'Ulya, Tri; Mardiani, Desika Putri; Nugroho, Rivo; Salim, Tisya Fajriatus; Islami, Zahwa; Puspitasari, Savira Widya (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: The dynamics of assignment and high mobility in military families present the complexity of roles that have the potential to affect the stability of relationships and family harmony. Although various studies have addressed stress and resilience in military families, the balance of women's roles is still rarely understood as an actively constructed relational mechanism. This study aims to explore women's experiences in building a balance of roles and analyze their contribution to the harmony of the military family. This study uses a qualitative approach with phenomenological design. Participants consisted of 15 wives of Army soldiers who were selected through purposive sampling techniques in the Greater Malang area. Data were collected through semi-structured in-depth interviews, limited observations, and documentation. The credibility of the data is maintained through triangulation of sources and techniques as well as the member checking process. Data analysis was carried out using Moustakas' phenomenological steps through the process of horizontalization, thematic grouping, and synthesis of the meaning of experience. The results of the study identified four main themes, namely domestic role negotiation, strengthening marital communication, emotion regulation, and community social support. The findings of the study show that role balance is built through adaptive relational processes and contributes to the stability of family interactions during military assignments. This study provides contextual empirical support for the study of the Role Theory and the quality of marriage in the socio-cultural context of the Indonesian military family. Abstrak: Dinamika penugasan dan mobilitas tinggi dalam keluarga militer menghadirkan kompleksitas peran yang berpotensi memengaruhi stabilitas relasi dan keharmonisan keluarga. Meskipun berbagai penelitian telah membahas stres dan resiliensi pada keluarga militer, keseimbangan peran perempuan masih jarang dipahami sebagai mekanisme relasional yang dibangun secara aktif. Penelitian ini bertujuan untuk mengeksplorasi pengalaman perempuan dalam membangun keseimbangan peran serta menganalisis kontribusinya terhadap keharmonisan keluarga militer. Penelitian ini menggunakan pendekatan kualitatif dengan desain fenomenologi. Partisipan terdiri atas 15 istri prajurit TNI Angkatan Darat yang dipilih melalui teknik purposive sampling di wilayah Malang Raya. Data dikumpulkan melalui wawancara mendalam semi-terstruktur, observasi terbatas, dan dokumentasi. Kredibilitas data dijaga melalui triangulasi sumber dan teknik serta proses member checking. Analisis data dilakukan menggunakan langkah fenomenologi Moustakas melalui proses horizontalisasi, pengelompokan tematik, dan sintesis makna pengalaman. Hasil penelitian mengidentifikasi empat tema utama, yaitu negosiasi peran domestik, penguatan komunikasi marital, regulasi emosi, dan dukungan sosial komunitas. Temuan penelitian menunjukkan bahwa keseimbangan peran dibangun melalui proses relasional yang adaptif dan berkontribusi terhadap stabilitas interaksi keluarga selama masa penugasan militer. Penelitian ini memberikan dukungan empiris kontekstual terhadap kajian Teori Peran dan kualitas perkawinan dalam konteks sosial budaya keluarga militer Indonesia.